RSL3 Drives Ferroptosis Through GPX4 Inactivation and ROS Production in Colorectal Cancer - Sui, Xinbing; Zhang, Ruonan; Liu, Shuiping; Duan, Ting; Zhai, Lijuan; Zhang, Mingming; Han, Xuemeng; Xiang, Yu; Huang, Xingxing; Lin, Haoming; Xie, Tian (Frontiers in Pharmacology, 2018)
Ferroptosis is an iron-dependent, oxidative cell death, and is characterized by iron-dependent accumulation of reactive oxygen species (ROS) within the cell. It has been implicated in various human diseases, including cancer. Recently, ferroptosis as a non-apoptotic form of cell death induced by small molecules is emerging in specific cancer types, however, its relevance in colorectal cancer (CRC) is unexplored and remains unclear. Here, we showed that ferroptosis inducer RSL3 initiated cell death and ROS accumulation in HCT116, LoVo and HT29 CRC cells over a 24 h time course. Furthermore, we determined that ROS levels and transferrin expression were elevated in CRC cells treated with RSL3 accompanied by a decrease in the expression of glutathione peroxidase 4 (GPX4), indicating an iron-dependent cell death, ferroptosis. Overexpression GPX4 resulted in decreased cell death after RSL3 treatment. Taken together, our results suggest that the induction of ferroptosis contributed to RSL3-induced cell death in CRC cells and ferroptosis may be a pervasive and dynamic form of cell death for cancer treatment.